ROSJA I „RESZTA ŚWIATA”: SOŁŻENICYNOWSKA RECEPCJA MODELOWA A MOŻLIWOŚCI UNIWERSALNEGO ODCZYTANIA EPOPEI CZERWONE KOŁO - Sidor, Monika (Acta Neophilologica, 2017)
This paper gathers Alexander Solzhenitsyn’s selected statements relating to the reception of his most significant work of art The Red Wheel. The conditions of “proper reading” are depicted in Solzhenitsyn’s interviews, journalistic texts and fragments of the narrative included in his epic. The author of the paper explores the writer’s requirements that concern the influence of literature and a reader’s response to the historical novel. The reconstruction of Solzhenitsyn’s model reception also enables to define the writer’s attitude towards his reader. The author of The Red Wheel believes in the social role of literature and the universal meaning of a literary text concentrated on truth, thus Solzhenitsyn’s approach stresses the ethical dimension of literature and the figure of writer as a guide.